Tungerækkende tungetaler - Børglum, Pia-Kamilla; Tobberup, Pia (K&K - Kultur og Klasse, 2006)
Making use of one’s gifts of tongues Ursula Andkjær Olsen’s Lulus sange og taler (2000) is characterised by its fragmentary form, consisting of separate text parts ranging from philosophical essays to intimate private confessions. The article tries to show that the observant reader actually can find a quite closely knitted inner texture connecting the disparate elements with each other, thematically as well as in the text’s enunciation, how strange this might appear at first glance.